PEMBERIAN PUPUK ORGANIK CAIR UNTUK MENGURANGI PEMAKAIAN PUPUK ANORGANIK PADA TANAMAN KACANG TANAH (Arachis hypogeae L.) - Susantidiana, Susantidiana; Aguzaen, Hendra (Universitas Muhammadiyah Palembang, 2015)
The objective of this research was to study of combine between liquid organic fertilizer (POC) from banana trunk and coconut fiber with anorganic fertilizer in relation to growth and increase production of peanuts. This research was conducted from April until September 2013, at Talang Kibang village, West Baturaja district Baturaja, South Sumatera, using factorial Ramdomized Complete Block Design. The treatment liquid organic fertilizer and anorganic fertilizer using four factor each. It consist of 16 treatments. i.e., without POC ferlizer(A0), 30 ml + 14 l (A1), 40 ml + 14 l (A2), and 50 ml + 14 l (A3). the D factor consist of without anorganic fertilizer (D0), 25 kg urea.ha-1 + 25 kg SP36.ha-1 + 12,5 kg KCl.ha-1 (D1), 50 kg Urea.ha-1 + 50 kg SP36.ha-1 + 25 kg KCl.ha-1 (D2), dan 75 kg urea.ha-1 + 100 kg SP36.ha-1 + 50 kg KCl.ha-1 (D3).The result showed that of the best combine in increased to production of peanuts is A0D3 (without POC and 75 kg/urea.ha-1 +100 kg SP36.ha-1+ 50 kg KCl.ha-1). The liquid organic fertilizer had increases production in treatment A1 (30 ml + 14 l ). The treatment of anorganic fertilizer is D3 (75 kg urea.ha-1 +100 kg SP36.ha-1+50 kg KCl.ha-1) have increase production of peanuts.